Chiral changes of cortical microtubule orientations in epidermls of sunflower hypocotyls. The effect of blue and red light - Agata Burian (Acta Societatis Botanicorum Poloniae, 2011)
Light and developmental processes affect the cortical microtubule (cMT) orientation. The cMT orientation with a special regard to its chirality was analyzed under the outer epidermal cell walls in different regions of sunflower hypocotyls kept in darkness and after irradiation with blue and red light. The results show that the cMT orientation depends on the cell position along hypocotyl, but generally cMTs are oblique. The oblique orientation has defined chirality: either of Z-form (right-handed) or S-form (left-handed). In the lower region of hypocotyls the Z-form dominates. After irradiation of hypocotyls with blue light this domination has been maintained and appeared also in the upper region. In contrast, after irradiation with red light the Z-form domination has not been apparent. It is proposed that in darkness, variations of cMT orientations in the epidermis along the hypocotyl are due to developmental processes, while blue and red light affect the cMT orientation via "shifting" these processes backward and forward, respectively.